The transformation of Polish rural areas since 1989 - Marek Kozak (Wieś i Rolnictwo)
This article focuses on an analysis of factors that have influenced structural change in Polish agriculture since 1989. The Republic of Poland was the only CEE country, pre-1989, which had 70% of its agricultural land in private hands. This turned out not to be a development asset as there were mostly small subsistence farms (ca 70%) at the core of Polish agriculture. This resulted in much of the rural area (except for that located in the vicinity of cities or renowned tourist centres) being dependant, to a large extent on both low-productive agriculture and agricultural policies. Now, after almost 25 years of transformation, structural change in agriculture (and rural areas) is slowing down as a result of EU Common Agricultural and National policies. The agrarian structure, dominated by subsistence farms, remains stable (average farm size below 10 hectares, in some South-Eastern regions NUTS 2 below 5 hectares). As a result rural areas are still in need of a deep restructuring and a modernization of economic structures.